Cultivating Tradition: Organizational Culture Integration In Dewa Yadnya Ceremony For Cultural Preservation Amidst Globalization: English - Lasmi, Ni Wayan; Sedana Putra P, Komang Widhya (Lembaga Dongan Dosen, 2024)
This study explores the integration of organizational culture in the Dewa Yadnya ceremony at Pura Paibon, Gunaksa Village, Klungkung, in response to the challenges of globalization and modernization affecting local cultural heritage. Organizational culture becomes pivotal in maintaining the continuity of local traditions amidst ongoing changes. Through a community service approach, methodological steps were taken to understand, plan, and implement the integration of organizational culture within the culturally nuanced religious ceremony. The research began with a comprehensive needs assessment, involving data collection on local cultural values and the identification of challenges and opportunities in organizational culture integration. Coordination meetings with local traditional leaders, community members, and the service team were crucial in formulating strategies tailored to meet the needs and expectations of the community. Implementation was carried out through physical and logistical preparations for the ceremony and the application of organizational culture principles. Continuous monitoring during the ceremony execution evaluated the intervention's impact and made adjustments based on community feedback. Findings highlight the importance of a collaborative approach in addressing cultural changes and supporting the sustainability of cultural heritage. Practical implications underscore the need for ongoing efforts to facilitate cross-cultural dialogue to maintain the relevance of cultural heritage in evolving contemporary societies. Thus, organizational culture integration strengthens the identity and sustainability of local culture in the era of globalization.